Disseminated Intravascular Coagulation - Al-Mondhiry, Hamid (Thrombosis and Haemostasis, 1975)
Review of the coagulation laboratory records and medical records at Memorial Sloan-Kettering Cancer Center over a three year period (1971-1974) revealed 89 patients with disseminated intravascular coagulation (DIC). The diagnosis of DIC was made if laboratory studies showed evidence of quantitative and qualitative changes in fibrinogen and significant thrombocytopenia. The patients included 19 with leukemia (17 acute), 3 with multiple myeloma, 15 with lymphoma, 46 with metastatic solid tumors, (10 lung, 9 breast, 8 gastrointestinal, 12 genitourinary, 7 miscellaneous) 4 with vascular tumors, and 3 without tumor. Other conditions which might have precipitated or initiated DIC such as gram-negative sepsis, liver impairment, or mucin secreting tumors were present in the majority of patients. Bleeding occurred in 75% of the patients and was fatal in 36%. Thromboembolism occurred in 22.5%. Thirteen percent were asymptomatic. Serum lactic dehydrogenase was elevated in over 75 % of the patients at the time of, or subsequent to the occurrence of DIC. Treatment with heparin was helpful in only three of twenty patients. Eighty percent of the patients died within one to over 30 days of the onset of DIC. Post mortem evidence of DIC was present in 18 of 43 autopsies. Results of this study indicate that DIC is a frequent complication of a wide variety of tumors and that its occurrence causes morbidity and mortality in a significant number of patients. Treatment with heparin is of little help unless remission is induced and the precipitating factor(s) are reversed.